Uterocervical angle versus cervical length in the prediction of spontaneous preterm birth in women with history of spontaneous preterm birth: a prospective observational study - Ahmed Mohammed Elmaraghy; Salma Mohamed Ahmed Shaaban; Mohammed Salah Elsokkary; Ibrahim Shazly Mohamed Amen Elshazly (BMC, 2023)
Abstract Background Preterm delivery is a leading cause of neonatal mortality and morbidity. History of spontaneous preterm birth is the greatest risk factor for another preterm delivery. So, every effort should be made to prevent the recurrence of preterm delivery in this vulnerable group. This study aimed to evaluate the predictive ability of the anterior uterocervical angle and cervical length in preterm birth. Patients and Methods This was a prospective cohort study that included 70 patients with a history of spontaneous preterm birth. Ultrasound measurements of cervical length and anterior uterocervical angle were set to be measured for each patient at three visits; first between 16 0/7 and 24 0/7 weeks, second between 24 1/7 and 32 0/7 weeks, and the third was between 32 1/7 and 36 6/7 weeks. The correlation between both measures and the prediction of preterm birth among study participants was the primary outcome of the study. Neonatal outcome among the study patients was a secondary measure of outcome. Results The incidence of preterm birth among study participants was 31.41%. Cervical length and uterocervical angle showed progressive decrease and increase respectively throughout pregnancy. At the 2nd visit, the two measures were significantly different between those who delivered at term and those with preterm delivery with the cervical length being significantly shorter in the preterm arm (3.0 ± 0.49 versus 3.38 ± 0.36, p < 0.001) and uterocervical angle being significantly bigger among the same arm (110.1 ± 18.48 versus 84.42 ± 12.24, p < 0.001). A uterocervical angle > 89.8° at the second visit predicted preterm birth with 81.8% sensitivity and 70.8% specificity while cervical length ≤ 3.22 cm at the second visit predicted preterm birth with 68.1% sensitivity and 62.5% specificity. Multivariant logistic regression analysis showed that uterocervical angle > 89.8° at the second visit increased the odds ratio for preterm birth by 9. Conclusion Uterocervical angle can be a useful ultrasound marker for the prediction of preterm birth among high risk patients. A cutoff value of 89.8° can be used as a threshold above which prophylactic measures such as cervical cerclage or progesterone therapy can be provided. Trial registration NCT05632003 (First posted date: 30/11/2022).